Charge screening strategy for domain pattern control in nano-scale ferroelectric systems - Tomoaki Yamada; Daisuke Ito; Tomas Sluka; Osami Sakata; Hidenori Tanaka; Hiroshi Funakubo; Takahiro Namazu; Naoki Wakiya; Masahito Yoshino; Takanori Nagasaki; Nava Setter (Scientific Reports, 2017)
Abstract Strain engineering is a widespread strategy used to enhance performance of devices based on semiconductor thin films. In ferroelectrics strain engineering is used to control the domain pattern: When an epitaxial film is biaxially compressed, e.g. due to lattice mismatch with the substrate, the film displays out-of-plane, often strongly enhanced polarization, while stretching the film on the substrate results in in-plane polarization. However, this strategy is of a limited applicability in nanorods because of the small rod/substrate contact area. Here we demonstrate another strategy, in which the polar axis direction is controlled by charge screening. When charge screening is maintained by bottom and top metallization, the nanorods display an almost pure c-domain configuration (polarization perpendicular to the substrate); when the sidewalls of the nanorods are metallized too, a-domain formation prevails (polarization parallel to the substrate). Simulations of the depolarization fields under various boundary conditions support the experimental observations. The employed approach can be expanded to other low-dimensional nano-scale ferroelectric systems.